4. Detection of Toxoplasma gondii infection by Polymerase Chain Reaction (PCR) and Histological Examination on Balb/c Mice - Muhammad Hanafiah; Dwinna Aliza; Erdiansyah Rahmi; Wisnu Nurcahyo (The International Journal of Tropical Veterinary and Biomedical Research, 2016)
The purpose of this research was to compare the use of PCR method and histological examination to diagnose toxoplasmosis in tissues of Balb/c mice infected with sporulated oocysts through drinking water. A total of 20 male Balb/c mice aged approximately 2 months were used in this experiment. Each mouse was infected with 1x103 Toxoplasma gondii tachyzoites intraperitoneally. Tissue samples (liver, lung, heart, kidney, and brain) were collected from 5 mice on day 1, day 5, day 7, and day 9 after infection. Samples were then examined by PCR and histological methods. The data collected were analyzed descriptively. The results showed that PCR method was more sensitive than histological examination. PCR examination using primer invitrogen gen can amplify DNA T. gondii at 436 bp of the samples from liver, lung, heart and brain on Day 7 and Day 9 after infection. The histological examination showed that the cyst of toxoplasma was found in the brain while mononuclear cells infiltration was found in other internal organs.